"A BONE OF CONTENTION…": BARRIERS AND SITUATIONAL DEPENDENCIES TO FOOD PREFERENCES OF NURSING HOME RESIDENTS. (11th November 2018) - Goldstein, C; Abbott, K M; Bangerter, L R; Kotterman, A; VanHaitsma, K S
Abstract: We all assign considerable physical and socioemotional values to food. Few studies examine how the intersectionality of these values impact food preferences among nursing home residents, and the links between food preference and nutritional intake. We interviewed 255 residents across 28 NHs regarding their food preferences using items from the Preferences for Everyday Living Inventory (PELI). Using content analysis, we identified n=381 perceived barriers. Major barriers mentioned included; provider schedules, provider polices, staff proficiency, and provider resources to what, when and where residents eat. Perceived health limitations and personal resources were also identified as barriers to obtaining snacks, take-out and dining out. The importance of food preferences changed depending on residents' perceived health and quality of family relationships. Results have implications for providers to centralize food preference in care planning in accordance with CMS New Dining Practice Standards, and to use food preferences to address dining quality concerns.